Beyond Temporal Causality: Synthesizing al-Ghazālī and Ibn Rushd’s Concepts of Time in Light of Tawasul through Kalām Falsafī - Agung Nugroho Reformis Santono; Achmad Ma’ruf Hidayatulloh; Sayyida Roychana Salma; Kurniawan Seno Aji (Aqlania, 2025)
This article explores the classical theological-philosophical debate between al-Ghazālī and Ibn Rushd regarding the eternity of the universe, time, and motion, focusing on the concepts of taqaddum zamānī (temporal precedence) and taqaddum rutbī (hierarchical precedence). While al-Ghazālī defends the temporal creation of the cosmos by divine will, Ibn Rushd maintains that the universe eternally exists in a hierarchical dependence on God. The study employs a kalām falsafī framework to critically reconstruct these opposing views and integrate them with the spiritual practice of tawasul, a living tradition in contemporary Muslim society that views time as an ontological continuum rather than a linear sequence. The article’s significant contribution is a philosophical-theological synthesis demonstrating how the metaphysical structures of time in Islamic thought can account for spiritual practices like tawasul, wherein the past remains active in shaping present and future realities. This approach avoids binary tensions between rationality and theology, and proposes a dialogical epistemology rooted in revelation and demonstrative logic. This study opens new pathways for philosophical discourse in Islamic studies by bridging metaphysical cosmology with lived religious traditions. It also highlights the need for further research into how concepts like taqaddum zamānī and rutbī can inform contemporary interpretations of time in quantum cosmology, mystical theology, and ritual theory.